Preoperative 3D printing planning technology combined with orthopedic surgical robot-assisted minimally invasive screw fixation for the treatment of pelvic fractures: a retrospective study - YuLong Jing; LiMing Chang; Bo Cong; JianHang Wang; MingQi Chen; ZhiFeng Tang; JingJie Luan; ZiYin Han; YangDe Liu; Tao Sun (PeerJ)
Objective To explore the advantages and effectiveness of preoperative 3D printing planning technology combined with orthopedic surgical robot-assisted screw placement in the minimally invasive treatment of pelvic fractures compared to orthopedic surgical robot-assisted screw placement alone. Methods A retrospective analysis of the clinical data of 29 patients with unstable pelvic fractures treated with orthopedic surgical robot-assisted percutaneous screw fixation from July 2021 to August 2023 was conducted. Among them, 13 patients who underwent preoperative 3D printing technology for screw planning were assigned to the experimental group, and the remaining 16 patients were assigned to the control group. All patients underwent screw fixation alone or combined with other fixation methods for fracture fixation. The application of preoperative 3D printing planning in orthopedic surgical robot operations was described. The intraoperative screw drawing time, invasive operation time, number of fluoroscopies during invasive operation, postoperative evaluation of screw accuracy, fracture healing, complications, and functional outcomes were recorded and compared between the two groups. Results All patients successfully underwent surgery, with one patient in the control group experiencing numbness in the sciatic nerve innervation area. All patients were followed up for 4–15 months, with an average of 8 months, and all fractures achieved healing. The experimental group had a total of 26 screws inserted, while the control group had 30 screws. In the experimental group, the intraoperative screw drawing time was 3.0 (3.0, 3.37) min, significantly shorter than 4.0 (3.6, 4.0) min in the control group (P < 0.05). The proportion of screws not penetrating the bone postoperatively was 88.5% in the experimental group, significantly higher than 63.3% in the control group (P < 0.05). In the experimental group, the postoperative screw position, compared to the planned screw position, had an average position deviation of 3.05 ± 0.673 mm and an average spatial angle deviation of 2.22 ± 0.605°. At the last follow-up, the Majeed score was used to assess function, with the experimental group having an excellent and good rate of 84.6%, slightly higher than 75.0% in the control group, but the difference was not statistically significant (P > 0.05). Conclusion In the treatment of pelvic fractures using screw fixation, preoperative 3D printing technology planning combined with orthopedic surgical robots, compared to orthopedic surgical robot-assisted screw placement alone, can significantly reduce intraoperative screw drawing time, decrease drawing difficulty, enhance screw placement accuracy, and does not increase invasive operation time or the number of fluoroscopies. This approach makes the surgery safer and is a method worth applying.